MENINGKATKAN KEMAMPUAN GURU DALAM MELAKSANAKAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI KELOMPOK KERJA GURU KECAMATAN BINAKAL KABUPATEN BONDOWOSO SEMESTER GANJIL TAHUN PELAJARAN 2022/2023: KELOMPOK KERJA GURU KECAMATAN BINAKAL KABUPATEN BONDOWOSO - ENY RAHAYU (Mitra Pendidikan, 2022)
The many achievements in various developments in the world of education aim to improve the quality of student learning outcomes. Every development or progress achieved is an alternative for the teacher to try to improve the quality of the learning carried out. Improving the quality of qualified teaching staff needs to be carried out in a programmed, structured and sustainable manner through professional development by school supervisors. Efforts to increase the ability of teachers need a place that is able to accommodate various problems faced by teachers in the learning process to be able to find ways to solve problems. In planning the learning process what is meant is that an educator in an educational unit is required to be able to develop lesson plans. Meanwhile, a professional development system that should be able to empower its existence is now increasingly being used such as the KKG forum as an activity to assist, serve, direct, or organize all activities in in achieving the goal. The research location is in the Foster School Cluster, Binakal District, Bondowoso Regency, which consists of 11th schools. This research resulted in the conclusion that the implementation of Information and Communication Technology-based academic supervision carried out in the Binakal Sub-District Development Group was able to improve the ability of teachers to carry out the learning process. This is because the academic supervision process carried out is adjusted to the characteristics of the teacher and begins through a process of coaching and training with colleagues.